2007
DOI: 10.1016/j.ijrobp.2007.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Head-And-Neck Hyperthermia Applicator: Experimental Phantom Verification and FDTD Model

Abstract: Purpose: Experimental verification of the feasibility of focussed heating in the neck region by an array of two rings of six electromagnetic antennas. We further measured the dynamic specific absorption rate (SAR) steering possibilities of this setup and compared these SAR patterns to simulations. Methods and Materials: By a specially constructed laboratory prototype head and neck applicator, including a neck mimicking cylindrical muscle phantom, we performed SAR measurements by electric-field Schottky-diode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
4
29
0
Order By: Relevance
“…This justifies the use of birdcage type RF coils for transmission and loop RF coils for reception at lower fields (B0≤3.0T), while dipole antennas are well suited as transmit/receive elements for UHF MRI at B0≥7.0T (31,(119)(120)(121) and above (122). The usage of dipole or "dipole-like" antennas as a targeted RF heating device is very well recognized by the hyperthermia community (104,(126)(127)(128). Recent reports demonstrated for the first time the feasibility of an integrated device that supports diagnostic MR, MR thermometry and localized RF hyperthermia using bow tie electric dipoles immersed in high permittivity dielectric (31).…”
Section: Integrated Systems or Thermal Mrmentioning
confidence: 99%
“…This justifies the use of birdcage type RF coils for transmission and loop RF coils for reception at lower fields (B0≤3.0T), while dipole antennas are well suited as transmit/receive elements for UHF MRI at B0≥7.0T (31,(119)(120)(121) and above (122). The usage of dipole or "dipole-like" antennas as a targeted RF heating device is very well recognized by the hyperthermia community (104,(126)(127)(128). Recent reports demonstrated for the first time the feasibility of an integrated device that supports diagnostic MR, MR thermometry and localized RF hyperthermia using bow tie electric dipoles immersed in high permittivity dielectric (31).…”
Section: Integrated Systems or Thermal Mrmentioning
confidence: 99%
“…The phantom was heated with phase-coherent RF radiation at 434 MHz using an MR-compatible laboratory prototype of the HYPERcollar RF hyperthermia applicator [29]. The heat applicator consists of two rings of six patch antennas optimised to give a minimum antenna reflection coefficient (S 11 ) at 434 MHz.…”
Section: Heating Experiments and Thermometrymentioning
confidence: 99%
“…The validation of SEMCAD X was earlier extensively reported by Paulides et al [14,25], where SEMCAD X was shown to correctly predict the location and size of a SAR focus in a cylindrical phantom, using both lateral and longitudinal SAR steering. For this study, extra tests using the cylindrical phantom were carried out only on orientation to ensure that a focus shift from VEDO was properly converted into a focus shift in the phantom.…”
Section: Verification Of Vedomentioning
confidence: 64%
“…Different factors influence this mismatch between simulations and clinical practice. Firstly, although validation studies have been carried out on phantoms [25,28] and more recently in patients [29], there is still a lack of validation of the complete patient and HYPERcollar set-up. Inter-patient variation of EM and thermal properties exists and could be a source of error.…”
Section: Discussionmentioning
confidence: 99%